KRITERIA MALCOLM BALDRIGE DI ERA REVOLUSI INDUSTRI 4.0 PADA PERUSAHAAN MEDIA CETAK DALAM UPAYA MENCIPTAKAN PERUSAHAAN UNGGUL DANBERKELANJUTAN DI YOGYAKARTA - Agung Sulistyo; Fitria Agustin Sri Arwandi (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2020)
The development of Information technology has e a wide-ranging impact on every business, including print media. The ease and speed of public in getting information is one of its own threats, plus competition between similar businesses is no less Great. The Baldrige Kriteria is a concept that can be used to evaluate performance, encourage and study of a company to be excellence and sustainable. Baldrige Criteria consist of 7 pillars, namely : Leadership, Strategic Planning, Focus on Consumer and markets, measurement analysis and knowledge management, focus on human resources, management of business processes and results. The purpose of this study was to analyse the application of the concept of Baldrige criteria in the printed media (PT. BP Kedaulatan Rakyat) in an effort to create excellence and sustainable companies. This study uses a qualitative methode with a descriptive approach that is integrated to the concept of Baldrige Criteria. Data collection in this study uses in-depth interviews, observation, documentary methods, visual materials and literature study. The subject of this study were several employees from variousparts of the company. Based on the research that has been done, the results show that the management of the company is not in accordance with the Baldrige Criteria. The results of the study explain that the attributes used have not been fully applied, so it is necessary to have an appropriate program to become a excellence and sustainable companies.